Effect of Emotional State on Nutrition Behavior in Working And Non-Working Women Living in Manavgat District. - Tayfur, Muhittin; Ulucay , Vahibe; Koseoglu, Sabiha Zeynep Aydenk (Progress in Nutrition, 2020)
BACKGROUND/OBJECTIVES: The aim of this study is to evaluate whether there is the relationship between these cases by comparing moods like depression, stress, anxiety, nutrition behaviors, food preferences and anthropometric measurements of working and non-working women living in Manavgat district. MATERIALS/METHODS: This study was conducted with total of 210 women, of whom 105 were working and 105 were not nonworking, between the ages of 25-45. Participant’s demoggraphic characteristics, antropometric measurements, food consumption over the last 24 hours, depression, anxiety and stress level, and nutritional behavior. RESULTS: The difference between stress, anxiety and cognitive restriction scores of working and non-working women was statistically significant (p <0.05). A statistically significant difference was found between BMI and uncontrolled eating and cognitive restriction scores in both working and non-working women. Uncontrolled eating, cognitive restriction and emotional eating were found to be correlated with energy, protein, carbohydrate and fat (p <0.05). It also differs in working and non-working women. CONCLUSIONS: These findings showed that negative moods of working and non-working women have been found to have adverse effects on their nutrition behaviors. Keywords: Dietary habits, eating behavior, feeding patterns, working women,